MILO/ENGOT-ov11: Binimetinib Versus Physician's Choice Chemotherapy in Recurrent or Persistent Low-Grade Serous Carcinomas of the Ovary, Fallopian Tube, or Primary Peritoneum - Monk, Bradley J; Grisham, Rachel N; Banerjee, Susana; Kalbacher, Elsa; Mirza, Mansoor Raza; Romero, Ignacio; Vuylsteke, Peter; Coleman, Robert L; Hilpert, Felix; Oza, Amit M; Westermann, Anneke; Oehler, Martin K; et al. (Journal of clinical oncology, 2020)
Low-grade serous ovarian carcinomas (LGSOCs) have historically low chemotherapy responses. Alterations affecting the MAPK pathway, most commonly KRAS/BRAF, are present in 30%-60% of LGSOCs. The purpose of this study was to evaluate binimetinib, a potent MEK1/2 inhibitor with demonstrated activity across multiple cancers, in LGSOC. This was a 2:1 randomized study of binimetinib (45 mg twice daily) versus physician's choice chemotherapy (PCC). Eligible patients had recurrent measurable LGSOC after ≥ 1 prior platinum-based chemotherapy but ≤ 3 prior chemotherapy lines. The primary end point was progression-free survival (PFS) by blinded independent central review (BICR); additional assessments included overall survival (OS), overall response rate (ORR), duration of response (DOR), clinical-benefit rate, biomarkers, and safety. A total of 303 patients were randomly assigned to an arm of the study at the time of interim analysis (January 20, 2016). Median PFS by BICR was 9.1 months (95% CI, 7.3 to 11.3) for binimetinib and 10.6 months (95% CI, 9.2 to 14.5) for PCC (hazard ratio,1.21; 95%CI, 0.79 to 1.86), resulting in early study closure according to a prespecified futility boundary after 341 patients had enrolled. Secondary efficacy end points were similar in the two groups: ORR 16% (complete response [CR]/partial responses[PRs], 32) versus 13% (CR/PRs, 13); median DOR, 8.1 months (range, 0.03 to ≥ 12.0 months) versus 6.7 months (0.03 to ≥ 9.7 months); and median OS, 25.3 versus 20.8 months for binimetinib and PCC, respectively. Safety results were consistent with the known safety profile of binimetinib; the most common grade ≥ 3 event was increased blood creatine kinase level (26%). Post hoc analysis suggests a possible association between mutation and response to binimetinib. Results from an updated analysis (n = 341; January 2019) were consistent. Although the MEK Inhibitor in Low-Grade Serous Ovarian Cancer Study did not meet its primary end point, binimetinib showed activity in LGSOC across the efficacy end points evaluated. A higher response to chemotherapy than expected was observed and mutation might predict response to binimetinib.